The Persian Miniatures Collection of the Rijksmuseum, A Hidden Treasure Trove - Sajadi, Forough, (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
The present book offers an elaborate art historical study of the collection of Persian miniatures at the Rijkmuseum in Amsterdam. The collection includes detached folios, which are the most significant in any Dutch collection. The artworks, catalogued thorougly in this book for the first time, range in date from the thirteenth century until the early twentieth century, and cover diverse subject matters.